Transcription Factor CTIP1/ BCL11A Regulates Epidermal Differentiation and Lipid Metabolism During Skin Development. Issue 1 (December 2017) - Li, Shan; Teegarden, Amy; Bauer, Emily; Choi, Jaewoo; Messaddeq, Nadia; Hendrix, David A.; Ganguli-Indra, Gitali; Leid, Mark; Indra, Arup
Abstract The epidermal permeability barrier (EPB) prevents organisms from dehydration and infection. The transcriptional regulation of EPB development is poorly understood. We demonstrate here that transcription factor COUP-TF-interacting protein 1 (CTIP1/BCL11A; hereafter CTIP1) is highly expressed in the developing murine epidermis. Germline deletion ofCtip1 (Ctip1 −/− ) results in EPB defects accompanied by compromised epidermal differentiation, drastic reduction in profilaggrin processing, reduced lamellar bodies in granular layers and significantly altered lipid composition. Transcriptional profiling ofCtip1 −/− embryonic skin identified altered expression of genes encoding lipid-metabolism enzymes, skin barrier-associated transcription factors and junctional proteins. CTIP1 was observed to interact with genomic elements within the regulatory region of the gene encoding the differentiation-associated gene, Fos-related antigen2 (Fosl2 ) and lipid-metabolism-related gene, Fatty acid elongase 4 (Elvol4 ), and the expression of both was altered inCtip1 −/− mice. CTIP1 appears to play a role in EPB establishment of via direct or indirect regulation of a subset of genes encoding proteins involved in epidermal differentiation and lipid metabolism. These results identify potential, CTIP1-regulated avenues for treatment of skin disorders involving EBP defects.